Realizing “Deconstructional” Justice Through Agrarian Civil Law Reform: A Review Of Jacques Derrida’s Theory - Sahlan; Miqat, Nurul; Susi Susilawati (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
Agrarian law in Indonesia has a long history influenced by various power regimes. However, it still faces challenges such as agrarian conflicts and inequalities in land distribution. This research aims to analyze the application of Jacques Derrida's deconstruction concept in the reform of Indonesian agrarian civil law, by identifying and evaluating critical aspects that need to be deconstructed to realize more substantive and inclusive agrarian justice. This study uses normative legal research methods with a conceptual approach, analyzing primary, secondary, and tertiary legal materials through literature studies, and applying qualitative analysis techniques including descriptive, interpretative, and critical analysis to examine the application of Jacques Derrida's deconstruction theory in Indonesian agrarian civil law reform. The research results show that Jacques Derrida's deconstruction concept can be applied in Indonesian agrarian civil law reform to achieve more substantive justice. This approach allows for the dismantling of existing agrarian legal structures, revealing inconsistencies and contradictions within them, and opening space for new, more inclusive interpretations. Critical aspects that need to be deconstructed include colonial legacies in agrarian law, dualism between customary and national law, inequalities in land tenure, unfair conflict resolution mechanisms, lack of integration between agrarian policies and environmental protection, and weak implementation of indigenous peoples' rights. Through the deconstruction of these aspects, agrarian law reform can be directed to create a more just, inclusive, and sustainable system, taking into account broader social, cultural, and economic contexts.. Keyword: Deconstruction, Agrarian, Justice, Reform, Derrida.